Profile of congenital malformations in a state in northeastern Brazil - Rodrigues, Rosa Patrícia Gomes Tenório Omena (2020)
The research aims to analyze the epidemiological profile of congenital malformations in the State of Alagoas from 2009 to 2018. It presents a quantitative approach with the type of ecological, descriptive, retrospective and transversal study. 3,269 births with congenital malformations were identified, with rates ranging from 4.99 to 7.69 per 1,000 live births, sociodemographic data showed that the maternal age group was 20 to 29 years (47.3%), with 8 to 11 years of studies (46.9%), single (43.3%), with more than 7 prenatal consultations (44.4%), single pregnancy (96.8%) and predominance of Cesarean delivery (62.3 %). Regarding the profile of births with congenital malformations, the male gender was prevalent in 55.7% of the cases, the brown color with 88.8% and the majority of them were born atherm (72.3%), the apgar in the 1st and 5th minute was 8 to 10. The most incident type of malformations observed was related to the musculoskeletal, nervous and genitourinary systems with percentages of 44.8%, 15.9% and 10.3%, respectively. It is concluded that in the studied period there was a gradual increase in the rates of congenital malformations and these data allow subsidies for clinical investigations of the possible causes of this morbidity, in addition to contributing to the implementation of preventive measures with intersectoral and multidisciplinary actions.